PROBLEMS OF ENSURING ENERGY POLICY IN UKRAINE IN WARTIME CONDITIONS - CHEKHOVSKYI, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Ukraine's energy policy has an extensive structure in which all elements interact to function. Management activities in the field of energy policy are not unambiguous and simple, as they require taking into account various aspects of the country's life. These include resource, technical, economic, environmental, organizational, administrative, managerial, social, innovative, political, geopolitical, security and other aspects, as well as ideological aspects of energy supply for vital needs and functions of the state, society and economy. In addition, energy policy activities can evolve significantly over time in the same country, depending on the dynamics of socio-economic, scientific and technological development, and the transformation of energy market models. In recent years, both Ukraine and the world have seen significant changes in the principles of energy sector regulation, and the range of methods of using energy as a tool for achieving political goals is expanding. In addition, the acceleration of economic processes in the world necessitates a rapid response to changes, which, when considering the transition to greening the economy, should be reflected in the state's energy policy. It is worth noting that the energy policy created in recent years is specified in the relevant EU directives, which is directly transferred to the legal regulations of the EU states. These regulations significantly create conditions and even force reorientation of energy companies' strategies, as well as cause changes in the behavior of energy consumers. To a large extent, the implementation of these changes is associated with the application of various types of innovations, especially technological and organizational ones. The purpose of the article is to analyze the problems of ensuring energy policy in Ukraine in wartime. In the course of the study, the following research methods were used: method of analysis, synthesis, systematization, comparison, abstract and logical method, statistical methods of studying economic processes. The article considers the reform of the energy policy of Ukraine, which is an integral part of economic and national security, a necessary condition for the development of the state; analyzes the "New Energy Strategy of Ukraine until 2035: Security, Energy Efficiency, Competition"; considers the basic configuration of the country's energy policy formula, which will help optimize the energy sector infrastructure in accordance with the European Union's energy efficiency directives; proposes principles of state regulation in the field of energy policy.
Keywords: strategy; energy policy; provision; wartime; threats to energy security; state regulation measures; national security